INTERVAL RUNNING EXERCISE REDUCES RUNNING TIME OF 800 METERS DASH WITHOUT CAUSING INCREASED LEVEL OF SGOT – SGPT IN MALE STUDENTS OF THE FACULTY OF SPORTS SCIENCES, MANADO STATE UNIVERSITY - Galatang, Alprodit; Alex Pangkahila, Jahja; Ngurah Nala, I Gusti; Tirtayasa, Ketut (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2012)
The effort to gain best achievement in sports by means of exercise has twodilemmatic sides, both for the coaches and sport promoters. On one side, exercise shouldbe done intensely and maximally, but on the other side, it is a known fact that excessiveand maximal exercises can damage the body organs. The purposes of this study were toobserve the side effects of interval running exercise of 800 meters, to find out level offatigue by examining lactate acid produced by each model, and to assess the negativeeffects on organs as indicated by the level of SGOT-SGPT. The exercise model appliedin the study comprised interval running of 2 x 800 meters, 4 x 400 meters, 8 x 200meters, 16 x 100 meters and one standard of comparison exercise, which was runningexercise of 2 x 800 meters with passive rest. This study was true experimental usingrandomized pre-test-post-test control group design. Samples of this study were 27 malestudents of the Faculty of Sports Sciences, Manado State University, who were dividedinto five groups. Group 1 was with interval running exercise of 2 x 800 meters. Group 2was assigned to interval running exercise of 4 x 400 meters. Group 3 was with intervalrunning exercise of 8 x 200 meters. Group 4 was with interval running exercise of 16 x100 meters. Group 5 as comparison standard was with running exercise of 2 x 800 meterspassive rest. All the exercise models were carried out for six weeks, each with afrequency of three times a week. Results of the study showed that the five groupsdemonstrated reduction of running time of 800 meters dash (p<0.05), lactate acidproduction differed in some of the groups (p>0.05), levels of SGOT and SGPT of allgroups did not show significant increase (p>0.05). From the above findings, it can beconcluded that all exercise models of interval running 2 x 800 meters, 4 x 400 meters, 8 x200 meters, 16 x 100 meters and 2 x 800 meters with passive rest lowered the runningtime of 800 meters dash and did not increase level of SGOT-SGPT.
Keywords: Interval running exercise, running time of 800 meters dash, lactate acid level, SGOT-SGPT levels